PENINGKATAN KEMAMPUAN BERBICARA BAHASA MANDARIN MENGGUNAKAN METODE PEMBELAJARAN KOOPERATIF MODEL TIME TOKEN ARREND MELALUI MEDIA GAMBAR PADA SISWA KELAS X SMA KEBON DALEM SEMARANG (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2018)
Speaking ability is one of four aspects which should be achieved, especially in learning Mandarin. Mandarin speaking ability and interest of study of X-1 students Kebon Dalem Semarang High School was still not quite good. Cooperative learning is an alternative way that can be to solve this problem. The example of cooperative learning is by using Time Token Arrend model by using picture as media, encourage students to actively speak Mandarin in Mandarin lesson. The objective of the study was to determine that the application of Time Token Arrend Method can really improve Mandarin speaking ability of class X students. This research method was classroom action research with two cycles. Each cycles required 2 meetings with 4 steps on each meeting, those are planning, action, observation and reflection. The result of the study showed: (1) students speaking ability in spoken test was improve (cycle 1 class average :66,19, completeness percentage 38,09% and there was an improvement in cycle 2 with class average 83,65% and completeness percentage 100%). The improvement from cycle 1 and cycle 2 was 17,46 or 26,38%. (2) the result of students answer quality behavior was improve (cycle 1 61,66 and it was improve on cycle 2 86,07). The improvement of students answer quality behavior was 24,41 or 39,59%. The conclusion if this study was the application of Time Token Arrend model as a cooperative learning can improve students speaking ability in Mandarin and also students’ behavior. Abstrak___________________________________________________________________Berbicara merupakan kemampuan yang ingin dicapai dalam pembelajaran bahasa Mandarin. Namun, kemampuan berbicara dan minat belajar siswa di SMA Kebon Dalem Semarang kelas X-1 masih kurang. Upaya dalam pemecahan masalah ini adalah dengan menerapkan metode pembelajaran kooperatif Time Token Arrend melalui media gambar untuk mendorong siswa aktif berbicara bahasa Mandarin dalam pembelajaran bahasa Mandarin. Tujuan penelitian ini yaitu untuk mengetahui apakah metode pembelajaran kooperatif Time Token Arrend dapat meningkatkan kemampuan berbicara bahasa Mandarin siswa kelas X SMA Kebon Dalem Semarang. Jenis penelitian ini adalah penelitian tindakan kelas menggunakan dua siklus. Setiap siklus terdiri atas dua pertemuan dengan empat tahap yaitu perencanaan, pelaksanaan, pengamatan dan refleksi. Hasil penelitian menunjukkan : (1)  kemampuan berbicara siswa pada tes lisan meningkat (siklus I rata-rata kelas  66,19, persentase ketuntasan 38,09% dan meningkat pada siklus II rata-rata kelas mencapai 83,65 persentase ketuntasan 100 %). Peningkatan nilai rata-rata siswa pada siklus I dan siklus II mencapai 17,46 atau 26,38%. (2) nilai kualitas jawaban observasi perilaku siswa meningkat (siklus I sebesar  61,66  meningkat  pada siklus II menjadi 86,07). Peningkatan nilai kualitas jawaban observasi perilaku siswa meningkat menjadi 24,41 atau 39,59%. Simpulan dari penelitian ini adalah metode pembelajaran kooperatif Time Token Arrend  melalui media gambar dapat meningkatkan kemampuan berbicara bahasa Mandarin dan perilaku baik siswa.